Radiology Finding of Endometriosis Malignant Transformation into Ovarian Clear Cell Carcinoma: A Rare Case - Soetanto, Astri; Mardiyana, Lies (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
ABSTRACT Introduction: One of the risk factors for ovarian cancer is endometriosis. The most prevalent type of ovarian cancer linked to endometriosis is ovarian clear cell carcinoma. The CT scan examination helps identify the type of treatment for each mass lesion and distinguishes endometriomas from other lesions. Case Presentation: MSCT was done on a 42 years old female with abdominal pain and distention over a year; showed a cystic mass (16HU) with solid component (36HU) partly unclear borders, irregular edges, with dimensions ± 14.3 x 16.8 x 16.3 cm in the pelvic and abdominal cavity, impression originates from the adnexas, when administered contrast shows an increased enhancement in contrast (83HU), also found free fluid density(17HU) in abdominal cavity, suggestive malignant ovarian mass. A pathology anatomy examination was done and confirmed clear cell carcinoma of the left ovary, endometriotic cyst in the right ovary, and external endometriosis in the omentum. Conclusion: Endometriosis rarely develops into clear ovarian cell carcinoma; the preoperative characterization of an ovarian cyst and the CT appearance of ruptured endometriotic cysts are comparatively distinct from those of burst functional cysts.